your first equation says that
x = 1-4y
so "substitute" 1-4y wherever you see x in the other equation
2(1-4y) + 7y = 3
2 - 8y + 7y = 3
-y = 1
y = -1
next sub that y = -1 back into the first equation
x = 1 - 4(-1) = 1+4 = 5
x = 1-4y
Starting with the first equation
since x = 1 - 4y
Plug that in to the second equation
2 -8y + 7y = 3
2 - y = 3
2/2 - y = 3/2
- y = 3/2
Since why can't be negative, move the negative over to the other side
y = -3/2
Okay we found what Y is now plug that into the first equation
x = 1-4(-3/2)
x = 1 + 6
x = 7
so the answer is (7,-3/2)
I'm pretty sure this is right, but I hope a real tutor comes and say for sure
Oh sorry, I did my math wrong and Divided instead of subtracting.
Answer this Question
ALGEBRA HELP - When solving the equation, what property was used to go from step...
Algebra 1 - -3x + 6 < 21 I need help in solving this problem step by step. ...
Algebra II - Solving the formula for the indicated variable. I=prt,for r I need ...
algebra 1 - I was just wondering if anybody could explain to me the steps in '...
algebra - would you help me write a logic application for andy has the cards1,5...
Algebra 2 - i need help, step by step, in solving for fractional coefficients. ...
algebra 1 - ELEMENTARY ALGEBRA #3 Page 23 Chapter 3 Lesson 3.02 Solving Multi-...
Algebra - 3x-2=0 Solving for x, need step by step instruction?
math/algebra - solve each of the following systems by substitution. 16) 5x -2y...
Algebra1 - I am solving for linear equations and I'm wondering if I did Step 3 ...